The social market economy as a model for sustainable growth in developing and emerging countries - Ralph M. Wrobel (Economic and Environmental Studies (E&ES), 2012)
After the fall of state socialism about two decades ago, democracy and market economies were assumed to diffuse worldwide. However, the American financial crisis of 2008, leading to a worldwide economic crisis caused increasing criticism of capitalism. As laissez-faire capitalism, Keynesianism and state socialism have failed during the last decades, economic policy makers are searching for alternative approaches. The author recommends the Social Market Economy, based on the thoughts of the German economist Walter Eucken and being introduced in West Germany after WW II. In this article, first the scientific framework of a Social Market Economy will be briefly described. Then, it will be discussed whether and how the seven constitutive principles defined by Eucken can be transferred adaptively to developing and emerging economies. Use will be made of North's institutional approach as well as the new approach of an Open Access Order by North / Wallis / Weingast. The question will be addressed whether the Social Market Economy can be a model for sustainable growth in developing and emerging economies.
Keywords: 330; Social Market Economy; sustainable growth; institutional systems; New Institutional Economics; Open Access Order; Walter Eucken